Enhancing the state’s role in clusterbased tea development - Memmedova, Parvin (Dunakavics, 2024)
Considering that the state has the opportunity to directly influence the formation of the basic income of tea producers in the agricultural sector and the quality of the product varieties they produce, it allows to significantly reduce the uncertainty that exists in tea farming. The article examines the determination of the objectives of producers and consumers facing the agrarian policy of the state in tea cultivation, the development of tea cultivation and the increasing of the role of the state. In the study, the importance of having conditions that provide conditions (communication between tea production and processing enterprises and state bodies and development of personnel training system) for the purpose of developing a competitive cluster of tea products is shown, and a systematic analysis of the formation of a competitive cluster is used. It is proposed to develop an organizational and economic interaction mechanism between the cluster participants in order to ensure the efficient operation of the tea products cluster and high competitiveness. The principles inherent in the formation of tea growing clusters are defined, the innovative character of the development in the formation of the cluster, the accessibility of the creation of conditions for profitable investments that ensure the increase of the competitiveness of the cluster participants in the regional and international market are emphasized. Based on different methodological approaches, it is suggested that the formation of a cluster consists of six stages. Given the main methodological principles of the formation of the tea product cluster, the possibilities of forming an effective agrarian policy of the state are limited without having basic knowledge about the current state of tea cultivation development. The value of the article is that the correct choice of the direction of solving the problems that formed it can have a significant impact on the competitiveness of tea products in Azerbaijan.